A novel five‐step synthetic route to 1, 3, 4‐oxadiazole derivatives with potent α‐glucosidase inhibitory potential and their in silico studies. Issue 12 (23rd September 2019) - Iftikhar, Muhammad; Shahnawaz,; Saleem, Muhammad; Riaz, Naheed; Aziz‐ur‐Rehman,; Ahmed, Ishtiaq; Rahman, Jameel; Ashraf, Muhammad; Sharif, Muhammad S.; Khan, Shafi U.; Htar, Thet T.
Abstract: A series of new N ‐aryl/aralkyl derivatives of 2‐methyl‐2‐{5‐(4‐chlorophenyl)‐1, 3, 4‐oxadiazole‐2ylthiol}acetamide were synthesized by successive conversions of 4‐chlorobenzoic acid (a ) into ethyl 4‐chlorobenzoate (1 ), 4‐chlorobenzoylhydrazide (2 ) and 5‐(4‐chlorophenyl)‐1, 3, 4‐oxadiazole‐2‐thiol (3 ), respectively. The required array of compounds (6a–n ) was obtained by the reaction of 1, 3, 4‐oxadiazole (3 ) with various electrophiles (5a–n ) in the presence of DMF ( N, N ‐dimethylformamide) and sodium hydroxide at room temperature. The structural determination of these compounds was done by infrared, 1 H‐NMR (nuclear magnetic resonance), 13 C‐NMR, electron ionization mass spectrometry, and high‐resolution electron ionization mass spectrometry analyses. All compounds were evaluated for their α‐glucosidase inhibitory potential. Compounds 6a, 6c–e, 6g, and 6i were found to be promising inhibitors of α‐glucosidase with IC50 values of 81.72 ± 1.18, 52.73 ± 1.16, 62.62 ± 1.15, 56.34 ± 1.17, 86.35 ± 1.17, 52.63 ± 1.16 µM, respectively. Molecular modeling and ADME (absorption, distribution, metabolism, excretion) predictions supported the findings. The current synthesized library of compounds was achieved by utilizing very common raw materials in such a way that the synthesized compounds may prove to be promising drug leads. Abstract : A series of new N ‐aryl/aralkyl derivatives of 2‐methyl‐2‐{5‐(4‐chlorophenyl)‐1, 3, 4‐oxadiazole‐2ylthiol}acetamide were synthesized and evaluated for their α‐glucosidase inhibitory potential. Compounds 6a, 6c–e, 6g, and 6i were found to be promising inhibitors of α‐glucosidase with IC50 values in the range of 86.35–52.63 µM. Molecular modeling and ADME (absorption, distribution, metabolism, excretion) predictions were used to characterize the mode of binding interactions and drug‐like properties of the active molecules.